Distributed event-triggered H∞ state estimation for T–S fuzzy systems over filtering networks. Issue 9 (June 2017) - Yan, Huaicheng; Xu, Xiaoli; Zhang, Hao; Yang, Fuwen
Abstract: This paper is concerned with the problem of distributed event-triggered H ∞ filtering over sensor networks for a class of discrete-time nonlinear system modeled by a set of linear Takagi–Sugeno(T–S) fuzzy models. In the filtering network, every individual filter receives the measurement information from the nonlinear plant, meanwhile, each filter can exchange the information with the other filters. Event-triggered communication scheme is applied to determine whether or not the current instant information should be transmitted to the quantizer. Distributed fuzzy filters are designed to guarantee the H ∞ disturbance attenuation level for the error estimation of the filtering network. Finally, a simulation example is provided to illustrate the effectiveness of the proposed filter design approach.